Challenges in Work with Adults : the Situation Analysis in Latvia - Vintere, Anna; Čerņajeva, Sarmīte; Koroļova, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the 21st century, people have to cope with continuous change and it is important that people could learn through-out their lives. To gain knowledge successfully throughout the lifetime, personality development psychology, personal needs and education motivation are seen as the more significant features. In order to identify the different age adults learning needs and motivation to learn, and to identify the learning characteristics, the article summarizes a number of case studies - situation analysis, which were done in the framework of Nordplus Adult Education Development project "How to challenge adults to teach adults".